LGV Analysis Of Hydroperoxy Radical (Ho2): Spectral Lines For Its Detection In A Cosmic Object - Chandra, S.
Knowing rotational and centrifugal distortion constants in conjunction with electric dipole moment for HO2 radical, we have calculated energies for rotational levels (without fine-structure splitting), and probabilities for radiative transitions between the levels. С помощью известных вращательных и центробежных констант аберрации, в сочетании с электрическим дипольным моментом для радикала HO2, были вычислены энергия вращательных уровней (без расщепления тонкой структуры) и вероятности радиационных переходов между уровнями.
Keywords: Astrophysics